In Vitro Efficacy of Antibiotic Combinations with Carbapenems and Other Agents against Anaerobic Bacteria - Takumi Umemura; Mao Hagihara; Takeshi Mori; Hiroshige Mikamo (Antibiotics, 2022)
We investigated the in vitro efficacy of combinations of carbapenems with clindamycin (CLDM) and minocycline (MINO) against Bacteroides fragilis and Peptostreptococcus species. We selected the carbapenems imipenem, meropenem, panipenem, doripenem, and biapenem. To evaluate the antibiotic efficacy of these combination regimens, the fractional inhibitory concentration index (FICI) was calculated against clinical isolates. Consequently, combination regimens of each carbapenem with CLDM or MINO showed synergistic or additive effects against 83.3–100.0% and no antagonistic effects against P. anaerobius isolates. However, against the B. fragilis group (B. fragilis, B. thetaiotaomicron, and Parabacteroides distasonis), although the combination with other carbapenems and CLDM or MINO did not show remarkable synergistic effects, the combination regimen of IPM with CLDM or MINO indicated mainly additive antibiotic efficacies (FICIs: >0.5 to ≤1.0) to B. fragilis groups. Then, antagonistic effects were admitted in only 5.6% of B. fragilis groups. The effectiveness of antibiotic combination therapy against pathogenic anaerobes has remained unclear. Then, our results can provide new insights to explore the effective combination regimens against multidrug-resistant anaerobic bacteria as empirical and definitive therapies, while this study used only carbapenem susceptible isolates. Hence, further studies are needed to use highly antibiotic-resistant anaerobic isolates to carbapenems.